Urtica dioica in the Management of Benign Prostate Hyperplasia (BPH) - Mahboubi, Mohaddese (Natural Products Journal, The, 2020)
Background: Benign Prostatic hyperplasia (BPH) is known as a disease prevalent in men after the age of 50 years old. Ninety percent of men with the age of 80 years and over have BPH. BPH is associated with functional problems like dysuria, nocturia, polyuria, urinary incontinence and recurrent urinary tract infections. Urtica dioica or nettle is a popular medicinal plant for management of BPH in men. Objective: This article evaluates the efficacy and safety of nettle and its related possible mechanisms in the management of BPH. Methods: For the preparation of this manuscript, all the information was gathered from accessible and inaccessible resources (Web, Books, Thesis, etc.). Results: The results of preclinical and clinical studies confirmed the efficacy of nettle roots extracts (methanol, ethanol, and petroleum ether) in the improvement of BPH in term of IPSS score, and patient's life quality. An increase in mean and maximum urinary flow rates and a reduction in prostate volume and residual urine level were observed after treatment with nettle extract. Nettle roots should be used for 6-12 months as its use is possible for a long time without any serious adverse effects. Conclusion: Designing the clinical trials to compare the efficacy of different extracts from roots or leaves and investigation of molecular mechanisms of action could be the approaches for future.
Keywords: urinary tract infections